Feasibility of an intensive control insulin-nutrition glucose model ‘icing’ with Malaysian critically-ill patient - Abdul Razak, Normy Norfiza; Ahamad, Nurhamim; Suhaimi, Fatanah M.; Jamaludin, Ummu; Md Ralib, Azrina (Innovare Academic Sciences Pvt Ltd, 2016)
A clinically verified patient-specific glucose-insulin metabolic model known as ICING is used to account for time-varying insulin sensitivity. ICING was developed and validated from critically-ill patients with various medical conditions in the intensive care unit in Christchurch Hospital, New Zealand. Hence, it is interesting and vital to analyse the compatibility of the model once fitted to Malaysian critically-ill data. Results were assessed in terms of percentage of model-fit error, both by cohort and per-patient analysis. The ICING model accomplished median fitting error of<1% over data from 63 patients. Most importantly, the median per-patients is at a low fitting error of 0.34% and per cohort is 0.35%. These results provide a promising avenue for near future simulations of developing tight glycaemic control protocol in the Malaysian intensive care unit.